High Rate of Failure After Matrix-Assisted Autologous Chondrocyte Transplantation in Osteoarthritic Knees at 15 Years of Follow-up. Issue 9 (July 2019) - Andriolo, Luca; Reale, Davide; Di Martino, Alessandro; Zaffagnini, Stefano; Vannini, Francesca; Ferruzzi, Alberto; Filardo, Giuseppe
Background: Chondral and osteochondral lesions in osteoarthritic knees of young patients remain challenging for orthopaedic surgeons, due to a combination of high functional demands and limited indications for joint replacement in this population. The possibility of extending the indication of cartilage regenerative procedures to these patients may allow the delay of metal resurfacing. Purpose: To analyze the potential of a cartilage regenerative approach to provide clinical benefits in young patients with osteoarthritic knees, documenting outcomes in terms of clinical improvement as well as failures, in particular regarding knee replacement, at long-term follow-up. Study Design: Case series; Level of evidence, 4. Methods: A total of 41 patients (mean ± SD age, 43 ± 9 years) who had cartilage lesions (4 ± 2 cm 2 ) in osteoarthritic knees (Kellgren-Lawrence grade 2 or 3) underwent matrix-assisted autologous chondrocyte transplantation (MACT) as a salvage procedure. Patients were evaluated with International Knee Documentation Committee (IKDC), EuroQol visual analog scale (EQ-VAS), and Tegner scores before surgery; at 1, 2, 5, and 9 years after surgery; and at a final follow-up at a mean of 15 years after surgery (range, 14-18 years). Failures were also recorded. Results: An improvement was observed in all scores after surgery, but a progressive worsening over time was noted. The mean ± SD IKDC score improved from 38.6 ± 16.2 to a maximum of 66.0 ± 18.6 at 2 years ( P < .0005), with a subsequent deterioration until the final evaluation at 56.2 ± 21.7 ( P = .024). A similar trend was confirmed by EQ-VAS scores. Tegner scores improved at all follow-up points but did not reach the preinjury level. Patients who underwent combined surgery obtained significantly lower results. Only 13 patients (32%) had an IKDC score higher than 70. During the follow-up period, 21 patients underwent reoperation (18 with knee replacement) and 3 more patients experienced clinical failure, for a total surgical and clinical failure rate of 59% at 15 years. Conclusion: The use of cartilage regenerative surgical procedures, such as MACT, as salvage procedures for young, active patients affected by chondral and osteochondral lesions in osteoarthritic knees led to a limited improvement, with the majority of patients experiencing failure at long-term follow-up. Although a minor subpopulation experienced favorable and stable improvement, the use of MACT for such a challenging indication remains questionable until responding patients can be profiled.